Peranan E-Government Dalam Mitigasi Dampak Perubahan Iklim - Suharnata, Suko; Shahrullah, Rina Shahriyani (Legal Spirit, 2023)
This legal scientific paper not analysis in depth role e-government in mitigating the impact of climate change in the Riau Islands region. As it is known that climate change is a serious topic of discussion for every country. The climate change that is happening in the Riau Islands region has an impact on almost all sectors ranging from health, agriculture, to changes in the number of islands in the Riau Islands. The preparation of this paper was carried out using normative and empirical methods through literature studies and interviews and observations so that the results of the analysis are described descriptively to find out the answers to the legal issues under study. The results of the research and discussion show that the impact of climate change in the Riau Islands over the past 20 years has triggered floods, extreme weather, extreme waves and abrasion, forest and land fires, and landslides. A number of risks resulting from these natural disasters can be prevented and minimized through mitigation measures by the Riau Islands Provincial Government. The e-government service through Kepri Smart Province has in fact not accommodated the public's need for disaster mitigation, so that currently the community still relies on two main mobile applications namely InaRISK Personal and BMKG Info. It is hoped that in the future the Riau Islands Provincial Government can develop and optimize the Riau Islands Smart Province service through the existence of a special service that provides information and early warning of disasters throughout the Riau Islands.